2021
DOI: 10.1177/0032258x211049335
|View full text |Cite
|
Sign up to set email alerts
|

A price paid? A review of the research on the impact of investigating serious crime on the wellbeing of police staff

Abstract: Research pertaining to the wellbeing of police focuses on the job at a macro level, neglecting that policing is an occupation made up of thousands of roles. The needs of staff in various roles differs according to the situations that they are exposed to. This paper provides a review of the literature pertaining to the impact of criminal investigation on employees’ wellbeing. Three discernible categories regarding the wellbeing of criminal investigators are revealed and the paper demonstrates that criminal inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
2
0
8
Order By: Relevance
“…This study has demonstrated that the levels of clinical symptoms experienced by the three groups of forensic practitioners confirmed the view of Cartwright and Roach (2021) that more attention should be given to the wellbeing of police staff. Forensic investigators should be regarded as being at a similar, if not higher, level of risk compared to their police officer colleagues.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This study has demonstrated that the levels of clinical symptoms experienced by the three groups of forensic practitioners confirmed the view of Cartwright and Roach (2021) that more attention should be given to the wellbeing of police staff. Forensic investigators should be regarded as being at a similar, if not higher, level of risk compared to their police officer colleagues.…”
Section: Discussionsupporting
confidence: 68%
“…Every policing role involves hazards; however, the dangers faced by a response officer are very different to that of a forensic scientist and a collision investigator (Cartwright and Roach, 2021). Each police officer or staff member will have unique vulnerabilities and resilience factors dependent on their life experiences, personality, support and training (Tehrani and Piper, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies support the notion that police work is highly stressful (9,(23)(24)(25)(26) and that police officers experience high levels of work-related stress relative to many other occupations (27). For example, working with traumatized victims and conducting homicide inquiries are stressors in the area of criminal investigation (28)(29)(30). Police work also involves shift work, traumatic events, staff shortages, and bureaucratic burden, all of which are considered stressful.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Asimismo, trabajar con víctimas vivas y vulnerables, especialmente menores, tiene más impacto emocional que con víctimas que ya han fallecido. Igualmente, escuchar revivir el evento traumático en las declaraciones puede generar este tipo de efectos negativos (Cartwright y Roach, 2022;Foley y Massey, 2021;Horvath y Massey, 2018;Roach et al, 2016;Simonovska et al, 2023).…”
Section: ;unclassified
“…Aunque se utilizan de manera indistinta, poseen matices que los diferencia. El primero no se experimenta de manera directa, pero provoca efectos idénticos que el Trastorno de Estrés Postraumático (TEPT) (Cartwright y Roach, 2022;Figley, 1995;Middleton, 2023;Perez et al, 2011). Entre ellos se encuentra la hipervigilancia, pensamientos intrusivos, revivir el evento traumático, evitación y adormecimiento o excitación persistente (American Psychiatric Association, 2013;Denk-Florea, et al, 2020;Figlley, 1995;World Health Organization, 2019).…”
unclassified